Rising Cesarean Rates of Twin Deliveries in Germany from 1990 to 2012 - Kyvernitakis, A.; Kyvernitakis, I.; Karageorgiadis, A. S.; Misselwitz, B.; Papaspyrou, G.; Kalder, M.; Schmidt, S. (Zeitschrift für Geburtshilfe und Neonatologie, 2013)
In the past 2 decades there has been an increasing trend for cesarean deliveries in twin pregnancies associated with increased maternal and fetal morbidity and mortality.We analyzed the mode of delivery of 18 132 twin gestations from the perinatal survey of Hessen in Germany between 1990 and 2012 and divided them into 4 categories according to the week of gestation (<28, 28–31, 32–36, >36). We further analyzed the cesarean delivery rates for the same period depending on the institutional level and divided them into 3 categories – University hospitals with perinatal center (U/PS), non-university affiliated hospitals with perinatal center (NU/PS) and smaller clinics without perinatal unit (NU/NPS).Cesarean rates changed from 63.6% (< 28), 88.9% (28–31), 59.6% (32–36) and 40% (> 36) in the year 1990 to 74.2%, 95.5%, 76.9% and 68.7% in 2012, respectively. As such, we report an overall increase of 23.5% in cesarean deliveries of twins over the last 23 years. We find an overall increase of 16.8%, 21% and 22.1% in university hospitals with perinatal units, in non-university hospitals with perinatal unit and in smaller hospitals without perinatal units, respectively. Furthermore, combined cesareans increased from 3.9% in 1990 to 7.0% in 2012.These findings indicate a dramatic increase in cesarean delivery rates for twin births from 1990 to 2012. We discuss the importance of international compatible guidelines for the conditions and technical procedures for twin deliveries.
Keywords: cesarean rates; twins; delivery